Analysis Of Differences In The Productivity Of Msmes Sentra Rajut As A Pandemic Impact Of Covid-19 - et. al., Agatha Rinta Suhardi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The resilience of Micro Small Medium Enterprises (MSMEs) in Indonesia is currently being tested in the face of the impact of the economic downturn due to the Covid-19 pandemic. This condition also resulted in a decrease in the productivity of the knitting centers of SMEs, including the Binong Jati knitting center in Bandung City, as a result of the Covid-19 pandemic. The purpose of this study is to analyze differences in productivity before the pandemic and after the pandemic has hit the world. The method used is to use a different test between two interconnected samples. The population in this study were MSMEs which are members of the Binong Jati Rajut Center with a sample of 9 MSMEs. Result From this study, from 9 MSMEs, only 3 MSMEs experienced an increase in productivity even though the pandemic took place. From the different tests carried out, it was found that there was no change in productivity between before and after the pandemic.